Effect of nitrogen and phosphorus on growth and yield of irrigated sunflower (Helianthus annuus L.)* - A. N, Ali, A.; E. Mohamed, I.; A. Babiker, E (Gezira Journal of Agricultural Science, 2021)
Experiments were conducted in winter (2000 2001) and summer (2001) seasons at Elrahad Research Station to investigate the influe- nce of four levels of nitrogen and two levels of phosphorus on growth characters and seed yield of two sunflower cultivars, viz Rodio and Hysun 33. Experiments were arranged in a randomized complete block design with four replications. Rodio and Hysun 33 varied in their growth characters. Differences between the two cultivars. Were highly significant for plant height, leaf area index, days to 50% flowering, days to maturity, head diameter, number of seeds per head, 1000-seed weight and empty seeds percentage. The two cultivars were siY1ificantly different in their seed yield. Nitrogen application significantly increased all growth characters and seed yield of the two cultivars, in both seasons, however, it decreased days to 50% flowering and days to maturity. Nitrogen fertilizer had no significant effect on empty seeds percentage. Phosphorus application signific- antly increased leaf area index, head diameter, number of seeds per head and 1000-seed weight. However, plant height, days to maturity and percentage of empty seeds were not affected. Application of phosphorus had no significant effect on seed yield.